Payment System Analysis Non Cash Loan in Order to Increase Net Cash Flow Company Operations and Supplier at PT Adhi Karya (Persero) Tbk Project Stone Crusher Sigli Toll - Banda Aceh - M Fakhri Ulsar Sirait; Rahima Br Purba; Oktarini Khamilah Siregar (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine Payment System AnalysisNon-Cash Loans In Order to ImproveNet Cash FlowCompany Operations andSupplierson PT Adhi Karya (Persero) Tbk ProjectStone CrusherSigli-Banda Aceh Toll Road. This research uses variablesnon-cash loan, with the dependent variableNet Cash FlowAnd suppliersas a moderating variable. The method used is descriptive method. This research uses secondary data obtained from IDX and documentation from collaborating companies. The population and sample in this research was the PT Adhi Karya (Persero) projectStone CrusherSigli-Banda Aceh Toll Road. This research aims to find out the payment systemNon-Cash Loansin order to improve Net Cash Flowcompany operations andsuppliers. The results of this research show that the systemnon-cash loanin order to improveNet Cash Flow the company's operations run smoothly and are profitable for PT Adhi Karya (Persero) Tbk and Suppliers. However, not many people still know the systemnon-cash loanand this financing facility has not yet been implemented by the Bank for lower middle class companies